5x+6y=67

Simple and best practice solution for 5x+6y=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6y=67 equation:


Simplifying
5x + 6y = 67

Solving
5x + 6y = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6y' to each side of the equation.
5x + 6y + -6y = 67 + -6y

Combine like terms: 6y + -6y = 0
5x + 0 = 67 + -6y
5x = 67 + -6y

Divide each side by '5'.
x = 13.4 + -1.2y

Simplifying
x = 13.4 + -1.2y

See similar equations:

| 7x(1/3xN)-4=10 | | 6x-3=14x-19 | | 4(z-3)=5-3z | | (7(1/3y))-4=10 | | (M)(10)=n | | 5x-10(x-2)=x^2 | | 3ab^2-6b= | | 15x=7x-(11-4x) | | 0.75x=24 | | X^72/8x4 | | 2p/3p | | 8.1a+2.3=5.1-3.1 | | 5b-5=7b | | y=-(x+9)2-15 | | 5(x+7)=10x+20 | | C=320+5+3 | | 50=2(2x-5) | | 1898-160= | | 2x-2(x+3)=-6 | | 1898-120= | | 4a+27=9a+8 | | (X+5)(x-5)=90 | | 3/5x-y=52 | | 17=x-2 | | 30b+30m=16b+44m | | -3-3=6 | | 4-1+2x+2x-3=5x+4 | | 12n-6=4n-10 | | 217=81-v | | 3x-cos(6x)=0 | | 535+.21x=585+.13x | | (2D/7)*T=D/2-(D/4)*T |

Equations solver categories